2010
DOI: 10.1063/1.3420245
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional character of whistler turbulence

Abstract: It is shown that the dominant nonlinear effect makes the evolution of whistler turbulence essentially three dimensional in character. Induced nonlinear scattering due to slow density perturbation resulting from ponderomotive force triggers energy flux toward lower frequency. Anisotropic wave vector spectrum is generated by large angle scatterings from thermal plasma particles, in which the wave propagation angle is substantially altered but the frequency spectrum changes a little. As a consequence, the wave ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 25 publications
2
92
0
Order By: Relevance
“…[15] Also noticeable in Figure 2 (bottom) are the multiple bands of diffuse, plasma waves that extend beyond the stronger, whistler sferics within the VLF band, possibly associated with lower hybrid waves [e.g., Kelley et al, 1985], or with enhanced turbulence caused by nonlinear scattering, as suggested by Ganguli et al [2010]. At this location, we calculate the lower hybrid frequency to be near 10 kHz, since the plasma was ∼90% Hydrogen, as determined by the onboard RPA measurements.…”
Section: Instrumentation and Data Examplesmentioning
confidence: 99%
“…[15] Also noticeable in Figure 2 (bottom) are the multiple bands of diffuse, plasma waves that extend beyond the stronger, whistler sferics within the VLF band, possibly associated with lower hybrid waves [e.g., Kelley et al, 1985], or with enhanced turbulence caused by nonlinear scattering, as suggested by Ganguli et al [2010]. At this location, we calculate the lower hybrid frequency to be near 10 kHz, since the plasma was ∼90% Hydrogen, as determined by the onboard RPA measurements.…”
Section: Instrumentation and Data Examplesmentioning
confidence: 99%
“…, and E kz = E kx kz k x , respectively, as shown in Ganguli et al [2010]. The resonant phase velocity, v res ! "…”
Section: ) Diminished Landau Damping Of Whistlers In the Solar Windmentioning
confidence: 99%
“…et. al 29 ), and they can be generalized as figure 7(b), the dispersion relation is sometimes referred as the electrostatic whistler waves. Finally, we suggest electron-ion hybrid (EIH) mode is a possible candidate of the LH mode.…”
Section: Discussion and Space Applicationmentioning
confidence: 99%